2009
DOI: 10.1038/eye.2009.170
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of pupil diameter after posterior chamber phakic intraocular lens implantation

Abstract: Purpose To observe the changes of pupil size over time after Visian Implantable Collamer Lens (ICL) implantation. Patients and methods We retrospectively examined 30 eyes of 23 consecutive patients undergoing ICL implantation. We measured the entrance and real pupil diameters using a Hartmann-Shack aberrometer (KR-9000, Topcon, Tokyo, Japan) before and 1 day, 1 week, and 1, 3, 6, and 12 months after surgery. We also investigated its relationship with the amount of vaulting using slit-lamp microscopy 1 year pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 37 publications
3
12
0
Order By: Relevance
“… 14 , 22 It was shown that there was also no significant correlation between pupil diameter changes and the ICL vault. This finding is in accordance with Kamiya et al’s study, 23 whose results showed no significant correlation between the entrance pupil diameter and the amount of vaulting after ICL implantation.…”
Section: Discussionsupporting
confidence: 93%
“… 14 , 22 It was shown that there was also no significant correlation between pupil diameter changes and the ICL vault. This finding is in accordance with Kamiya et al’s study, 23 whose results showed no significant correlation between the entrance pupil diameter and the amount of vaulting after ICL implantation.…”
Section: Discussionsupporting
confidence: 93%
“…The vault after ICL V4c implantation was essentially equivalent to the vault after ICL V4 implantation, suggesting that the presence of the central hole did not significantly affect the postoperative vault. With regards to the short term changes after surgery, we found a significant association between the vault changes and the pupil size changes from 1 day to 1 month after the implantation of both ICL V4 and ICL V4c IOLs, concluding that pupil size change is a critical factor in vault change, which is consistent with previous relevant studies [1216, 18, 24]. We also found a relatively high vault 1 day after surgery in a select number of eyes with small pupils.…”
Section: Discussionsupporting
confidence: 91%
“…Several studies [1215] have shown that pupil constriction leads to a significant decrease in central vault under photopic conditions, as it causes ICL movement posteriorly towards the crystalline lens. These findings have been supported by Du et al [16] who demonstrated similar outcomes during pharmacological accommodation with the use of topical pilocarpine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several previous studies have reported that changes in pupil size in response to certain stimuli, such as photopic light exposure or during accommodation, are associated with postoperative vaulting [ 24 26 ]. In a previous study, we demonstrated that pupil constriction in response to photopic light exposure creates an antero-posterior vector via iris constriction, in which the iris exerts pressure on the ICL [ 23 ].…”
Section: Discussionmentioning
confidence: 99%